Analysis of The Teacher'S Role in Learning Management in a Talent-Based Curriculum - Rilci Kurnia Illahi; Rahmi Yunita; Wahidul Basri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The talent-based curriculum is a school-specific curriculum developed by SMA INS Kayutanam. This curriculum guides principals and teachers to develop their learning management. The purpose of this research is to analyze the teacher's role in learning management in the talent-based curriculum that has been implemented in the school. The approach used is a qualitative approach with a case study research method. Data collection tools in this study are interviews and observation. The results of the study concluded that the teacher's role in talent-based curriculum management: a) learning planning, which is seen in the preparation of talented lesson plans and syllabus b) implementation of learning as a learning facilitator to control students so they do not make uniform work, and c) assessment of learning outcomes carried out namely the assessment of the competency-based testing system approach. The implications of the research are to be carried out by the SMA INS Kayutanam by conducting professional teacher development in the development of a school-specific curriculum.